The role of fabric banners for community engagement in digital era - Zainol, R.; Goh, H.C.; Mohd, I.; Nordin, N.A.; Baharom, S.M.; Hamzah, T.A.A.T. (Malaysian Institute of Planners, 2015)
This paper presents the role of fabric banners as a communication medium for community engagement, which would be the relevant communication medium for public participation in the development plan process. Discussions are based on findings from a study conducted in Subang Jaya-USJ, Selangor where the main objective was to evaluate the relevance of fabric banners as a communication medium in eliciting public participation in community engagements. The study was within a theoretical framework that links community engagement, urban way of life and the Media Richness Theory. Primary data were collected through self-administered survey under the purposive sampling method and in-depth interviews involving 100 local residents of Subang Jaya-USJ. Findings demonstrated that fabric banners are still relevant and functioning as an effective communication medium in community engagement, particularly in Subang Jaya-USJ. Thus, this type of communication medium should be seriously considered in town planning public participation process.